Altered Functional Connectivity of Hypothalamus in Lifelong Premature Ejaculation Patients. Issue 3 (18th February 2020) - Gao, Ming; Feng, Nana; Wu, Jiayu; Sun, Jianhua; Zhang, Lei; Guo, Xinlong; Yuan, Jianlin; Guo, Jun; Liu, Peng
Abstract : Background: As one of the most prevalent sexual dysfunctions in men, lifelong premature ejaculation (PE) often leads to patient distress. The hypothalamus is implicated in the ejaculatory control of healthy males. However, we do not know whether the hypothalamus‐related intrinsic connectivity is altered in lifelong PE patients. Purpose: To investigate abnormal intrinsic connectivity of the hypothalamus in lifelong PE patients compared with healthy controls (HCs). Study Type: Prospective pilot study using cross‐sectional data of patients and HCs. Subjects: Forty‐seven lifelong PE patients and 30 HCs were included in this study. Field Strength/Sequence: 3.0T MRI scanner for T1 ‐weighted imaging using spoiled gradient recalled echo sequence and functional imaging using a single‐shot gradient recalled echo sequence. Assessment: Preprocessing of MRI data and hypothalamus‐seeded functional connectivity (FC) computation were performed using DPABI4.1. Statistical Tests: The two‐sample t ‐test within SPM12 was adopted to examine possible alterations of intrinsic connectivity of hypothalamus in lifelong PE patients compared with HCs including anxiety and depression scores as covariates (false discovery rate‐corrected, P < 0.05). The correlation analysis was then used to assess possible associations between the imaging findings and clinical features in the patient group (Bonferroni‐corrected, P < 0.05). Results: Compared with HCs, lifelong PE patients had decreased hypothalamus‐seeded FC in the left orbitofrontal cortex, bilateral insula, superior temporal cortex, superior temporal pole, middle temporal cortex, left fusiform, right parahippocampal gyrus, and right cerebellum. The intravaginal ejaculatory latency time positively correlated with the mean z‐score from the hypothalamus‐insula ( r = 0.45) and hypothalamus‐cerebellum ( r = 0.48) intrinsic connectivity, separately. Data Conclusion: We have shown that hypothalamus‐seeded FC alterations and the correlations between the aforementioned abnormal FC alterations and intravaginal ejaculatory latency time. The current findings may promote the understanding of the hypothalamus‐related neural mechanisms involved in the abnormal ejaculatory information processing in lifelong PE patients. Level of Evidence: 1 Technical Efficacy Stage: 3 J. Magn. Reson. Imaging 2020;52:778–784.